2021
DOI: 10.1155/2021/9250967
|View full text |Cite
|
Sign up to set email alerts
|

ICD Pocket-Site Infection Secondary to Gonococcal Bacteremia: The First Reported Case

Abstract: Introduction. Cardiovascular implantable electronic devices (CIEDs) are being increasingly used in the primary and secondary prevention of malignant ventricular arrhythmias and conduction system disorders. Infectious complications associated with CIEDs include infective endocarditis, lead infections, and pocket-site infections, primarily involving Staphylococcus species. Infective endocarditis is a rare but life-threatening complication of gonococcal bacteremia. We report the first case of a CIED pocket-site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Neisseria gonorrhea endocarditis is a rare complication of DGI and represents less than 0.1% of such cases. 1 , 2 , 3 Although CIED pocket infection has been reported in DGI, 4 to our knowledge this is the first report of CIED-associated gonococcal endocarditis. Acute and subacute CIED infections are typically attributed to coagulase-negative Staphylococcus, whereas chronic infections are largely caused by S. aureus (50%) and coagulase-negative staphylococci (50%) in more than 95% of cases.…”
Section: Discussionmentioning
confidence: 87%
“…Neisseria gonorrhea endocarditis is a rare complication of DGI and represents less than 0.1% of such cases. 1 , 2 , 3 Although CIED pocket infection has been reported in DGI, 4 to our knowledge this is the first report of CIED-associated gonococcal endocarditis. Acute and subacute CIED infections are typically attributed to coagulase-negative Staphylococcus, whereas chronic infections are largely caused by S. aureus (50%) and coagulase-negative staphylococci (50%) in more than 95% of cases.…”
Section: Discussionmentioning
confidence: 87%
“…An estimated 1-2% of patients with DGI can develop endocarditis and, in rare cases, may be the sole manifestation of DGI. In addition, there has been a case of a cardiovascular implantable electronic device infection with associated bacteremia due to N. gonorrhoeae [ 12 ]. From our review of PubMed and Google Scholar, there are no other reported cases of mediport or other central venous catheter infections due to N. gonorrhoeae .…”
Section: Discussionmentioning
confidence: 99%